SMU celebrates the graduation of its 15th and largest batch - Singapore Management University (Institutional Knowledge at Singapore Management University, 2018)
Singapore Management University (SMU) kicked off four days of graduation celebration for the Class of 2018 today at the Opening Ceremony of SMU Commencement 2018. The ceremony, which was graced by Guest-of-Honour Mr Heng Swee Keat, Minister for Finance, was held on SMU campus today with 1,000 graduates, award winners, as well as family and friends of the graduates in attendance.